Implementation Restorative Justice in Criminal Cases at Investigation Level - Mujahid Mujahid; Sri Kusriyah (Law Development Journal, 2020)
The objectives of this study are: 1. To analyze implementation restorative justice in the settlement of criminal cases at the investigation level at the Pati Police Resort at this time. 2. To analyze the constraints that arise in implementation restorative justice in the settlement of criminal cases at the investigation level at the Pati Police. 3. To analyze restorative justice in the settlement of criminal cases at the investigation level at the Pati Police in the future. The research method used is juridical empirical. Types / Specifications of Research, Types of Data and Data Sources, Data Collection Methods, Data Analysis Methods. Research results and discussion: Handling of criminal cases by the Police (investigators) at the Criminal Investigation Unit of the Pati Police with criteria including the category of criminal offenses punishable by criminal sanctions of up to 1 (one) year must be prioritized to apply diversion, criminal acts subject to sanctions. a sentence of more than 1 (one) year to 5 (five) years of the Pati Police Criminal Investigation Unit is carried out with the criteria, among others, considering the law enforcement process in accordance with the applicable positive law and if the settlement is through restorative justice. The use of restorative justice by the police in solving criminal cases at the level of future investigations can represent a logical step in public service and general case handling reform. This contributes to improved community police relations. New participatory programs can encourage a form of direct accountability to the communities they serve. Police officers can apply the principles of restorative justice to develop sustainable collaborative partnerships with the community.